2002
DOI: 10.1155/s1064744902000194
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Five Different Diagnostic Techniques inMild‐to‐Moderate Pelvic Inflammatory Disease

Abstract: Objective: To evaluate the clinical diagnosis of pelvic inflammatory disease (PID) compared with the diagnosis of PID made by laparoscopy, endometrial biopsy, transvaginal ultrasound, and cervical and endometrial cultures. Study design: A diagnostic performance test study was carried out by cross-sectional analysis in 61 women. A group presenting PID (n = 31) was compared with a group (n = 30) presenting another cause for non-specific lower abdominal pain (NSLAP). Diagnosis provided by an evaluated method was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 21 publications
1
22
0
3
Order By: Relevance
“…If patients do not respond by 48-72 h or if the mass persists after standard antibiotic therapy, surgical treatments are required. Antibiotic treatment fails in 12-76% of patients with pelvic abscess [8,9,16,17]. In a study by Topcu et al [5], 79.8% (87/109) patients were managed surgically or discharged after 7 days of antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…If patients do not respond by 48-72 h or if the mass persists after standard antibiotic therapy, surgical treatments are required. Antibiotic treatment fails in 12-76% of patients with pelvic abscess [8,9,16,17]. In a study by Topcu et al [5], 79.8% (87/109) patients were managed surgically or discharged after 7 days of antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy is one established way to reach a correct diagnosis, although the overall diagnostic accuracy of this method is also unsatisfactory (32). A weakness of laparoscopy is that it will not detect endometritis and may not identify intratubal inflammation (33). Moreover, laparoscopy is an invasive technique that necessitates hospitalization and general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…One classic study [30] found a wide range of reliability in PID diagnosis comparing clinical findings, laparoscopy, transvaginal ultrasound, endometrial biopsy, and endometrial culture (Table 1). Current research is evaluating the possibility of microbiota existing in the upper genital tract in a physiologic state and its potential link to PID [31].…”
Section: Diagnosismentioning
confidence: 99%